Multicountry and Regional Macroeconometric Models; Makroekonometryczne modele gospodarki sẃiatowej i modele regionalne - Władysław Welfe (Comparative Economic Research. Central and Eastern Europe, 2012)
Multicountry models were developed in the previous century to serve the analyses and projections of the world economy and/or its regions (for instance Latin America). They distinguish the largest countries and the rest of the world (ROW) composed of particular countries. Hence, their structure is based on the specifications of equations for individual countries using full statistical information available at the countries level. The regional macroeconomic models are built for either administrative or geographical units distinguished within large countries (USA, China, Russia). Their structure should be in principle similar to those of the national economy. However, the statistical information of the regional economies is typically uncomplete: no sufficient information is available on exports and imports of the region, migrations and financial flows. Appropriate approximations are necessary. As in majority of countries the prices and wages movements are in general unified over the country, the variables representing the national level excerpt an impact on the regional variables. The regional impact on the national variables is rather unusual. The paper shows the skeleton model applied in the multicountry models and the skeleton of the macroeconomic regional model. The specific properties of the regional model are discussed and the possibilities of its extensions analysed. – – Modele gospodarki sẃiatowej lub jej czesći (regionoẃ) zostały zbudowane w ubiegłym stuleciu, słuzȧc celom analizy rozwoju i prognozowaniu gospodarki całego sẃiata lub wyroźṅionych regionoẃ (np. Ameryki Łacinśkiej). Modele te zwykle wyroźṅiały najwieksze, uprzemysłowione kraje sẃiata oraz sumarycznie pozostałe kraje (ROW). Stad ich struktura została oparta na specyfikacjach roẃnant́ypowych dla poszczegoĺnych krajoẃ, wykorzystujac pełnie statystycznych informacji gromadzonych dla kazḋego kraju. Makroekonometryczne modele regionalne sa budowane albo dla wyroźṅionych jednostek administracyjnych albo geograficznych w obrebie na ogoĺ duzẏch krajoẃ (USA, Chiny, Rosja, etc.). Ich struktura winna bycźblizȯna do struktury modeli danych krajoẃ. Jednakzė, dane statystyczne dotyczace regionoẃ sa na ogoĺ niekompletne: brak jest danych o eksporcie i imporcie regionu, migracjach ludnosći, przepływach finansowych etc.. Wymaga to odpowiednich aproksymacji. Poniewazẇ wielu krajach dynamika cen i plac przebiega w sposob́ podobny w skali kraju - wprowadza sie do modeli regionalnych zmienne dotyczace całego kraju. Z drugiej strony oddziaływanie zwrotne wystepuje na ogoĺ rzadko w tych modelach. W referacie przedstawiono typowe struktury makroekonometrycznych modeli wystepujacych w modelach gospodarki sẃiatowej oraz struktury modeli charakterystyczne dla modeli regionalnych. Specyficzne własnosći modeli regionalnych sa przedmiotem odrebnej dyskusji a takzė mozl̇iwosći rozbudowy tych modeli sa analizowane.
Keywords: 330